Engineered Biosynthesis of a Complete Macrolactone in a Heterologous Host - Kao, Camilla M.; Katz, Leonard; Khosla, Chaitan (Science (American Association for the Advancement of Science), 1994)
Macrocyclic polyketides have been subjects of great interest in synthetic and biosynthetic chemistry because of their structural complexity and medicinal activities. With expression of the entire 6-deoxyerythronolide B synthase (DEBS) (10,283 amino acids) in a heterologous host, substantial quantities of 6-deoxyerythronolide B (6dEB), the aglycone of the macrolide antibiotic erythromycin, and 8,8a-deoxyoleandolide, a 14-membered lactone ring identical to 6dEB except for a methyl group side chain in place of an ethyl unit, were synthesized in Streptomyces coelicolor. The biosynthetic strategy utilizes a genetic approach that facilitates rapid structural manipulation of DEBS or other modular polyketide synthases (PKSs), including those found in actinomycetes with poorly developed genetic methods. From a technological viewpoint, this approach should allow the rational design of biosynthetic products and may eventually lead to the generation of diverse polyketide libraries by means of combinatorial cloning of naturally occurring and mutant PKS modules.